Linguistical transformations of identity - Pažėraitė, Aušra Kristina (Religija ir kultūra, 2009)
In this paper I presented an analysis of a recent religious movement in Russia, called “The Old Russian Pravoslavian Old Believers – inglingian Church“ (Древнерусская церковь православных староверов-инглингов). This neo-pagan movement, whose founder, Alexander Yuryevich Hinevich, using a variety of linguistic manipulation and “Slavonic Vedas” of unknown origins, increasingly spreading up in paper and electronic format, – is trying ambitiously justify his doctrine of the genetic origins of ancestors of Slavic (having in mind Russian) – Aryan peoples going down to gods (namely Perun) for many hundreds of thousands, if not millions, years ago, who descended here, on the planet Earth from other planets, and occupied the northern hemisphere. Slavic-Aryan culture, in accordance with his doctrine (and of the rest of close to his church neo-pagan authorities, in particularly that of Trehlebov’), has been a real originator of all great civilizations in the World, but during the time of introduction of Christianity in Russia other nations “have robbed their history and their cultural advancements” trying to destroy their national memory by imposing them degraded self-images... In this study is presented analysis of “linguistic approach” of Hinevich, which revealed, that he uses a series of interpretative methods of Jewish Kabbalah, which fit naturally to semitic languages, but not so well to Indo-European ones. What results in distortion made by Hinevich of Russian language rules to fit those interpretative methods, not neglecting to explain that these techniques are also old Russian techniques, which were from them took off. As a possible prototype of these Kabbalistic methods was presented some examples from the Zohar with commentaries.
Keywords: ingliizm; Kabbalah; hermeneutics; racism; neopagans